Screening athletes with Down syndrome for ocular disease - BEKİROĞLU, GÜLNAZ NURAL (My University, 2010)
Background: Persons with Down syndrome are well known to have a high prevalence of vision and eye health problems, many of which are undetected or untreated primarily because of infrequent ocular examinations. Public screening programs, directed toward the pediatric population, have become more popular and commonly use letter or symbol charts. This study compares 2 vision screening methods, the Lea Symbol chart and a newly developed interactive computer program, the Vimetrics Central Vision Analyzer (CVA), in their ability to identify ocular disease in the Down syndrome population. Methods: Athletes with Down syndrome participating in the European Special Olympics underwent an ocular screening including history, auto-refraction, colour vision assessment, stereopsis assessment, motility assessment, pupil reactivity, and tonometry testing, as well as anterior segment and fundus examinations to evaluate for ocular disease. Visual acuity was tested with the Lea chart and CVA to evaluate these as screening tests for detecting ocular disease as well as significant, uncorrected refractive errors. Results: Among the 91 athletes that presented to the screening, 79 (158 eyes) were sufficiently cooperative for the examination to be completed. Mean age was 26 years ±10.8 SD. Significant, uncorrected refractive errors (≥1.00 spherical equivalent) were detected in 28 (18%) eyes and ocular pathology in 51 (32%) eyes. The Lea chart sensitivity and specificity were 43% and 74%, respectively, for detecting ocular pathology and 58% and 100% for detecting uncorrected refractive errors. The CVA sensitivity and specificity were 70% and 86% for detecting pathology and 71% and 100% for detecting uncorrected refractive errors. Conclusion: This study confirmed the findings of prior studies in identifying a significant presence of uncorrected refractive errors and ocular pathology in the Down syndrome population. Screening with the Lea symbol chart found borderline sufficient sensitivity and specificity for the test to be used for screening in this population. The better sensitivity and specificity of the CVA, if adjusted normative values are utilized, appear to make this test sufficient for testing Down syndrome children for identifying both refractive errors and ocular pathology. © 2010 American Optometric Association.
Keywords: Contrast sensitivity; Down syndrome; Public screening